Karakteristik Pasang Surut Laut di Pulau Jawa - H Haryono; Sri Narni (Faculty of Engineering, Universitas Gadjah Mada, 2004)
Sea tides are cailsed by atlraction of heavenly bodies especially moon and sun to the envelope of sea water of lhe earth. At different places of the earth, sea tides characteristics are different.Sea tides raw data collected from several sea tides stations in Java island are processed using sea tides computer software and amplitudes of sea tidal constants are determined. Based on Formzal formula, Formzal numbers are calculated, and sea tides characteristics areinterpreted. Linking lhe sea tides characteristic infurnntion to the digital map of Java island, sea tides characleristics map is discovered.The result of the research is information on sea tides charateristics for Jova island. Normally, mixed sea lides characteristics are discovered in Java island. Many users, e.g. hydrographic surveyors, fishermen, coaslal engineers, elc. need sea tides characteristics information for their works.Keywords: sea lides, Formzal nurnbers, Java island.